Digitalization in the Maritime Logistics Industry: A Systematic Literature Review of Enablers and Barriers - Fangli Zeng; Anqi Chen; Shuojiang Xu; Hing Kai Chan; Yusong Li (Journal of Marine Science and Engineering)
Digitalization is gaining its popularity in the maritime logistics sector due to its potential to enhance information sharing and automation. These advantages can significantly improve efficiency and have the potential to replace complex manual tasks. However, the diffusion of digitalization faces certain challenges, which, in turn, has drawn the attention of researchers. Implementing digitalization is a complex process, as it is affected by various enablers and barriers, while research providing a comprehensive overview of digitalization in the maritime logistics sector is limited. This study aims to fill the gap by conducting a literature review that reveals digitalization’s enablers and barriers in the maritime logistics sector and constructs a theoretical framework. It analyzes 117 articles that have made significant contributions to this field. The development of innovative technologies, such as blockchain, digital twins, and autonomous shipping, fosters digitalization in maritime logistics. Conversely, barriers like the lack of awareness about the benefits of digitalization can slow down its progress. In total, this paper identifies 19 enablers of and 10 barriers to digitalization in the maritime logistics sector. These enablers and barriers are classified into three groups–technology, organization, and environment–following the Technology–Organization–Environment (TOE) framework. We develop a theoretical framework accordingly using, as its basis, relevant innovation diffusion theories and studies. This study contributes to the development of effective digitalization strategies for maritime organizations and provides a theoretical foundation for future research.